2008
DOI: 10.2174/156652408785160934
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Channel Expression and Functional Diversity in the Immune Cells of Allergic Diseases

Abstract: Chloride channels are involved in many different physiological processes such as cell migration, proliferation and apoptosis. The importance of the CLC family of chloride channels in these cellular functions has been recognized only recently. Infiltration of inflammatory cells, such as eosinophils, T cells, mast cells and neutrophils, is a hallmark of allergy and asthma. Indeed, chronic asthma is associated with widespread damage to the bronchial epithelium, due to excessive apoptosis, and with defective epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…For example, because GAT-1 belongs to the Na ϩ -and Cl Ϫ -dependent transporter family solute carrier family 6, its activation might induce Cl Ϫ flux. Previous studies have revealed that Cl Ϫ channels are widely involved in physiological processes such as cell proliferation, apoptosis and migration (38). Therefore, it is necessary to investigate whether Cl Ϫ flux is involved in GAT-1 mediated T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, because GAT-1 belongs to the Na ϩ -and Cl Ϫ -dependent transporter family solute carrier family 6, its activation might induce Cl Ϫ flux. Previous studies have revealed that Cl Ϫ channels are widely involved in physiological processes such as cell proliferation, apoptosis and migration (38). Therefore, it is necessary to investigate whether Cl Ϫ flux is involved in GAT-1 mediated T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…proteinuria, aminoaciduria, glycosuria, phosphaturia, hypercalciuria, nephrolithiasis, and progressive renal failure (2735). In general, CLC channels have been demonstrated to contribute to a host of biological and cellular processes, including cell migration, proliferation, and apoptosis (36). Only CLC-3 has been shown to play a critical role in TGF-β–induced apoptosis of human airway epithelial cells and has recently been shown to be involved in the recruitment and activation of immune cells in the respiratory tract (36, 37).…”
mentioning
confidence: 99%
“…In general, CLC channels have been demonstrated to contribute to a host of biological and cellular processes, including cell migration, proliferation, and apoptosis (36). Only CLC-3 has been shown to play a critical role in TGF-β–induced apoptosis of human airway epithelial cells and has recently been shown to be involved in the recruitment and activation of immune cells in the respiratory tract (36, 37). However, the specific role of CLC-5 and/or cellular mediators that modulate important immune functions to trigger downstream signaling pathways has not yet been defined.…”
mentioning
confidence: 99%
“…Volume sensitive chloride channel CLC3 is involved in neutrophil [35] migration, but the detailed underlying mechanism still has not yet been deciphered [36]. Moreover, chloride and potassium channels might work in concert with each other [37] in order to achieve the optimal volume change in cell migration [10].…”
Section: Introductionmentioning
confidence: 99%